The effect of the waste management themed summer program on gifted students' environmental attitude, creative thinking skills and critical thinking dispositions - Ceylan, Ozge (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
With this study, the contribution of the waste management themed summer program, which includes enriched activities considering the learning needs of gifted students, has contributed to the students' environmental attitudes, creative thinking skills and critical thinking dispositions. A five-day program was applied to gifted (n = 29) fifth grade students. Data were collected by means of scales before and after the program and paired samples were analyzed by t-test. As a result of the analysis, it was found that the applied program created a difference in favor of the posttest, on students' environmental attitudes, creative thinking skills and critical thinking dispositions. One of the important results of this study is that summer programs, which are among the out-of-school learning environments, contribute to the attitudes and cognitive development of gifted/talented students.
Keywords: Gifted students; waste management; environmental attitude; thinking skills; EDUCATION; BACCALAUREATE; OUTDOORS; Education & Educational Research